Description of a new fossil Thelyphonida (Arachnida, Uropygi) and further record of Cratosolpuga wunderlichi Selden, in Selden and Shear, 1996 (Arachnida, Solifugae) from Crato Formation (Aptian/Albian), Araripe Basin, Brazil - William Santana; Allysson P. Pinheiro; Thiago Andrade Silva; Daniel Lima (PeerJ, 2024)
Background A new fossil species of whipscorpion, Mesoproctus rayoli n. sp., is described. The specimen originates from the Crato Formation, dating to the Lower Cretaceous (Aptian/Albian) period within the Araripe Sedimentary Basin. This species has been provisionally assigned to Mesoproctus Dunlop, 1998, as it represents the sole known Thelyphonida fossil genus discovered in South America and within Araripe Lagerstätte. Methods The material underwent detailed description and illustration processes. Key diagnostic characters, such as body length, pedipalpal coxae apophysis, the form of the opisthosoma, and the length of leg IV, were meticulously examined. SEM methods were applied in this study. Results Through the detailed analysis, comparisons and differences to Mesoproctus rowlandi Dunlop, 1998 were made possible. Additionally, a well-preserved specimen of the rare camel spider, Cratosolpuga wunderlichi Selden, in Selden and Shear, 1996, was identified from the limestones of the Crato Formation. The newly discovered fossil specimen of Cratosolpuga wunderlichi suggests two characters not previously described: (i) a segmented tarsomere on leg IV; and (ii) a leg I with one tarsal claw.